Formação em agroecologia: um estudo das práticas educativas do curso de Tecnólogo em Agroecologia da Escola Agrotécnica (EAGRO) da Universidade Federal de Roraima (UFRR) - Coutinho, Janailton (2018)
This research has sought to discuss the education topic in Agroecology technological course at Federal University of Roraima’s agro-technique school, in Boa Vista-RR. This dissertation’s objective was the pedagogical project of this course. The basic concepts evidenced in this thesis were agroecology, pedagogical practices and degree in agroecoly, which through this field research were turned into central categories. The search’s issue started from the following question: what’s the contribution of the formative project of the UFRR’s technological course in agroecology to the professional practices of its egresses. From this issue went through the subsequent objective: analyse the contribution of the pedagogical project from UFRR’s technological course in agroecology to the professional practices of its egresses, in order to strenghten an education that provides the human being’s integrality, in a relation of mutual respect between the scientific knowledge and native knowledge, considering the subject’s history and culture, in harmony with the enviroment. As specific targets, I’ve sought to know the course’s pedagogical project, identifying the related components to Agroeocology, its fundaments and proposals; identify the Agrocology’s concept in the pedagogical project, and lastly reveal the inseption of the egresses and their contribution to economic and socioenvironmental’s transformation to settlements and encampments of agrarian reform, listening to the egresses and their own families. The theoretical frame conceptual based in formation concepts, vocational training, field education, Agroecology and its pedagogical practices. In terms of methodological reference was the qualitative research, and the method used was the dialectical and phenomenological. The type of research was the descriptive and explanatory, with strablishment in the study’s case form. Participant observation, semi-structured interviews and visits to varied social groups and egresses’s families were used as research tools. A recorder was used as well as a field journal to record the information surveyed, and to analyse the data the content analysis. The main findings were based in the pedagogical project’s analysis and in the egresses’s social practices. They’ve shown that the alternation was used as an essential fundament of the maintenance of these young people in the field and in the university; a formation base on the technical perspective and distant from the social practices and settlements’s politics; an understanding from Agroecology as a produtive matrix and not as either a multidisciplinary or interdisciplinary science, based on the popular knowledge dialogued with the scientific knowledge and, the finally, a formation that has been focused on the technical principles/productives and distant from Agroecology’s extensions and sustainability. This research work’s conclusion suggests Agroecology education occurs from a wide base, multi, inter and transdisciplinary, and that values socioenvironmental knowledge and practices from peasants and workers, and agricultural workers, Agroecology makers.